AGRICULTURA FAMILIAR, SEGURANÇA ALIMENTAR E POLÍTICAS PÚBLICAS: análise da execução do Programa de Aquisição de Alimentos (PAA) na comunidade Itapari/Panaquatira do município de São José de Ribamar/MA no período de 2011 a 2015. - REIS, Adriana Jardim Castro Rocha dos (2017)
This dissertation analyzes the implementation of the Food Acquisition Program (PAA) in the Itapari/Panaquatira community of the municipality of São José de Ribamar/MA and its influence on family agriculture and food security in the region. The proposed discussion focused on understanding the perceptions about the program and the possible improvements in the quality of life and agricultural production from the implementation of the PAA in the said community by the municipal public power and, with this, to observe if the purpose of one of the governmental actions Of recent character in the midst of national social development policies has fulfilled its purpose. It was based on the main hypothesis that the PAA constitutes a public action that expresses the modification of social dimensions, in the municipality of São José de Ribamar. It is based on secondary assumptions that the reality of family agriculture and food security in Brazil, in Maranhão and in the municipality of São José de Ribamar is undergoing a process of weakening due to the strengthening of agribusiness; That in the municipality of São José de Ribamar, at the Itapari/Panaquatira poles, the implementation of the PAA constitutes a political feasibility of mitigating this weakening and restructuring of the family production modes of agriculture, so as to generate impacts on the social reality of the farmers The main objective was to analyze the perception of the family farmers of the Itapari/Panaquatira poles inserted in the Food Acquisition Program (PAA), from 2011 to 2015. The research followed a qualitative approach and contemplated two fronts of approach Methodological approach to obtaining and confronting data: one based on a bibliographical basis through the collection of governmental data and theoretical references that had the PAA and its socioeconomic impacts as object of study; And one of a more specific and dedicated to obtaining information in loco, in which semi-structured interviews were applied to the family farmers of Itapari/Panaquatira registered as suppliers of the PAA. The comparison of information obtained in the field together with the discussions presented by other studies reveals that the PAA brought productive and structural transformations of the Itapari/Panaquatira pole and that can be translated as positive and concerning the purpose highlighted by public policy as a tool for development and coping with social inequality. However, impasses and discontinuities instituted by local government managers have compromised the achievement of better performance, as highlighted by the farmers' testimony of the community studied in São José de Ribamar and as evidenced in critical trials that have observed the use of the PAA in National experiences in a way that is distorted to its original attribution.